Dermatoscopy of folliculosebaceous cystic hamartoma - Emiko Watanabe-Okada; Yuichi Kurihara; Shunichi Miyakawa; Masaru Tanaka (Mattioli1885, 2014)
A 29-year-old Japanese man presented to our institution with a nodule on his nose that had increased in size since childhood. Physical examination indicated the presence of an elastic, firm, pedunculated red nodule measuring 15 mm in size. Dermatoscopic examination of the nodule indicated a yellowish-white network, yellowish-orange dots/globules at its center, and a pinkish-white structureless peripheral area. Histopathological examination of an excisional biopsy specimen showed a dilated infundibulocystic structure with sebaceous lobules proliferating radially, surrounded by fibrous stroma. Moreover, mature adipocytes and small vessels were noted in the stroma. Based on these histopathologic findings, the patient was diagnosed with folliculosebaceous cystic hamartoma.